CGIAR 2030 Research and Innovation Strategy: Transforming food, land, and water systems in a climate crisis - CGIAR System Organization (CGIAR System Organization, 2021)
Food unites the world, and powers us forward. Today a powerful and unified global effort is needed to equip food systems to advance human and planetary health to their full potential. The climate crisis is at the forefront of threats to our ability to provide good nutrition for all people while staying within environmental limits. Interlocked with climate change are land degradation, deforestation, loss of biodiversity, depletion of water resources, and pollution. These threats to our planetary life support systems in turn propel poor health, economic inequality, social upheaval, and conflict. Food systems are both a driver and a victim of these challenges.